Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Construction du sujet-femme et imaginaire dissident : Largo desolato de Václav Havel - Deret, Anne (Université du Québec à Montréal, 1997)
Keywords: 1900-1999; 1980-1989; IREF; discipline; europe; mémoires/thèses; périodes historiques; régions géographiques; république tchèque; science politique; science politique et droit; théâtre

Démocratie et représentation - Riot-Sarcey, Michèle (Kimé, 1995)
La représentation politique est aujourd’hui en crise : partout en Europe, la légitimité des représentants est contestée, sans pour autant que la démocratie, en son principe, soit mise en cause. A partir de ce constat, des chercheurs des différentes disciplines ont questionné la représentation dans son actualité politique et dans sa formation historique. L’usage de la représentation, la délégation d’autorité qu’elle suppose, la violence qu’elle engendre, la domination qu’elle implique, la pratique démocratique qu’elle présuppose ont été soumis à examen par les intervenants au colloque organisé par le Centre Culturel de l’Albigeois. Les disfonctionnements et les apories d’une démocratie, longtemps considérés comme une donnée perfectible, se révèlent comme un simple produit des règles d’un système exclusif, qui contribuent largement à tenir à l’écart des pouvoirs et des lieux de représentation politiques les femmes comme la grande majorité d’une population, par ailleurs de plus en plus politisée.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; interdisciplinarité; occident; premier cycle; périodes historiques; représentation politique; science politique; science politique et droit; sciences humaines; théories féministes

Une victoire à la Pyrrhus ? : la lutte pour le droit à l’avortement - Lamoureux, Diane (Avortement : pratiques, enjeux, contrôle social, 1993)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; discipline; histoire des femmes*; histoire et politique; justice reproductive; militance; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Un genre trouble: le féminisme, la pornographie, la réforme du droit et la thèse de la reproduction de l'ordre social - Lacombe, D. (Déviance et société, 1992)
L'étude de la campagne de criminalisation de la pornographie au Canada, dans les années 1980, pose un défi au savoir conventionnel qui s'est développé, en sociologie et en criminologie, sur la réforme du droit. Ce savoir est l'argumentation selon laquelle les réformes, en dispersant le contrôle social, ne font que légitimer le système sans le modifier fondamentalement. Afin d'éviter l'essentialisme de ce savoir, j'ai utilisé une approche reflexive qui pense la relation entre la réforme du droit et le pouvoir comme à la fois contraignante et facilitante. L'établissement d'un lien entre la pornographie et la déviance sociale n'apparaît pas comme une construction sociale unifiée, mais comme un terrain contesté dans lequel se produisent des rapports de pouvoir complexes, et une multiplicité de stratégies de résistance. C'est dans ce sens que la réforme apparaît comme un mécanisme générateur des pratiques.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; canada; cours; criminologie; discipline; droit; féminisme pop; justice sociale; pornographie; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; thématiques

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach–in which pornography is defined as sex discrimination and therefore a violation of civil rights–would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance–what it is, what it does, what it means, how it works. Answers to the lies about it–lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." –from Pornography and Civil Rights
Section: 142 pages ; 22 cm
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis